Development of an Automatic Door Access Control System Using Fingerprint and Passcode Verification Technology - Uguru-Okorie, D. C.; Aribisala, A. A.; Adebimpe, A. M.; Fagbohun, O. O.; Ojaomo, K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Access control systems are essential in modern security architecture, yet traditional methods such as mechanical locks and single-factor authentication remain vulnerable to duplication, spoofing, and environmental limitations. To address these challenges, this paper presents the development of an automatic door access control system that integrates fingerprint biometrics with passcode verification on an Arduino platform. The major contribution of this work lies in its dual-factor authentication design, which enhances security while maintaining affordability, scalability, and ease of use. The system was implemented using an AS606 fingerprint sensor for biometric enrollment and verification, complemented by a keypad for passcode input and an intruder alarm for intrusion response. Experimental results demonstrated that the fingerprint scanner reliably captured and matched minutiae with confidence scores ranging from 0 to 255, and that thumbprints provided higher accuracy rates than index fingers, with a maximum accuracy of 70%. The integration of a secondary passcode layer and an intruder alarm further improved the robustness of the system compared to existing single mode solutions. Future work will explore the integration of additional biometric modalities and IoT-based monitoring to expand functionality. Overall, this study demonstrates that dual-factor authentication on an open-source platform offers a practical, secure, and cost-effective solution for modern access control.